Diversifikasi menjadi Produk Selai dan Peningkatan Mutu Jus Aloe Vera di SIGMA Food Sawangan Depok - Ismiyati Ismiyati; Ratri Ariatmi Nugrahani; Tri Yuni Hendrawati (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2018)
Community engagement activities, science and technology development for community for one of the partner SIGMA Food, Sawangan, Depok, has been done with purpose to overcome the priority problems, which are improving quality and quantity of Aloe vera juice products and diversification of Aloe vera products into jams. The abdimas team, act as the facilitator and instructor, has trained/accompanied (a) quality improvement training/counseling for Aloe vera juice by preservative addition; (b) quality improvement of Aloe vera juice in SIGMA Food by pasteurization and sterilization; and (c) diversification of Aloe vera jam product processing. The result of this training is known for improving partner’s understandings in (a) quality improvement of Aloe vera juices by preservative addition, bottle packaging sterilization process, and Aloe vera juice pasteurization; and (b) diversification of Aloe vera products.